NAFTA, Investiture and Redistribution. The Power Underpinnings of Trade and Investment Liberalization in Canada - Jordan Brennan (The Bichler and Nitzan Archives, 2012)
Criticism of trade and investment liberalization (TAIL) in North America has drawn attention to weak economic performance, wage-profit redistribution, social dumping and fiscal pressure on government programs as evidence that the TAIL regime has failed to deliver on some of its key promises. This criticism has been unable, however, to establish satisfactory conceptual and empirical connections between the dramatic distributional changes witnessed in the TAIL era and the reorganization of power that the TAIL regime entrenched. This paper will undertake a quantitative assessment of the Canadian political economy to see who the main beneficiaries of the TAIL era have been, contrasting returns to labor and to capital in the pre-TAIL and TAIL eras. Employing tools from radical institutionalism, two pictures are painted: the first picture examines broad changes in the distribution of income and the second picture examines differential business performance. The evidence from this inquiry suggests that although the official purpose of TAIL was to enhance the prosperity of all Canadians, this trade deal actually represented—both in its intentions and consequences—a political-economic transformation written by dominant capital, for dominant capital.
Keywords: 330; Canada; capital as power; distribution; differential accumulation; dominant capital; globalization; trade and investment liberalization